Pengaruh Ekstrak Kulit Manggis (Garcinia Mangostana Linn) Sebagai Antioksidan Terhadap Tikus Model Aterosklerotik - Muhammad Dicky Hafisalevi; Meddy Setiawan; Djanggan Sargowo (Jurnal Kardiologi Indonesia, 2012)
Backgrounds: Atherosclerosis defined by accumulation of Low density Lipoprotein (LDL) and inflammatory cells in tunica intima triggered by oxi-dative stress. Oxidative stress increase the level of Malondialdehid(MDA) which its activity inhibited by superokside dismutase (SOD) as endogenous antioxidant. Extract from pericaps of mangosteen has antioxidants activity that can inhibit the release of free radicals through reactive oxygen species (ROS) are characterized by increased levels of SOD and decrease levels of MDA rats serum. Objectives: aim of this research is to evaluate effect of extract from pericarp of mangosteen (Garcianna mangostana Linn) as antioxidants in rats models of atherosclerosis.Methods: The subjects of the research were 30 white rats (Rattus novergi-cus Strain wistar), divided into 5 groups (negative control, positive control, administration of extract  from pericarp of mangosteen 200, 400, and 800 mg/kg, p.o for 90 days) exploying True Experimental with The Post Test Only Control Group Design.The parameters used in this study is the SOD and MBA are read using spectrophotometry and analyzed by test of ANOVA, BNT1% test, using correlation and regression test.Results and discussion: Based on the statistic analysis, the value of MDA is MDA (r= -0,809; Sig = 0,000 < 0,01 and 2=0,655) and SOD(r = 0,565; Sig= 0,000 < 0,01 and 2=0,391). Whereas oral administration (800 mg/kg) dose of extract from pericap of mangosteen has a good result by increasing the level of SOD and decreasing the level of MDA.Conclusion: This research suggests that extract from pericarp of mangosteen may be potent antioxidant.